2013
DOI: 10.1177/0954406213489652
|View full text |Cite
|
Sign up to set email alerts
|

Material removal monitoring in precision cylindrical plunge grinding using acoustic emission signal

Abstract: A mathematical model of the acoustic emission signal during a grinding cycle is proposed for the monitoring of material removal in precision cylindrical grinding. Acoustic emission signals generated during precision grinding are sensitive to forces in grinding and present opportunities in accurate and reliable process monitoring. The proposed model is developed on the basis of a traditional grinding force model. Using the developed model, a series of experiments were performed to demonstrate the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…According to the accuracy theory of grinding machines and the accuracy theory of three-coordinate measuring instruments, as well as Equations (11) and (12), a "Double Accuracy As shown in Figure 3, coordinate system O 50 ; O 60 ; O 70 ; O 80 is respectively an integral coordinate system, a worktable translation coordinate system, a measuring probe rotation coordinate system and a measuring beam translation coordinate system. According to the theoretical solution method of grinding machine precision, it is also concluded that:…”
Section: Double Accuracy Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the accuracy theory of grinding machines and the accuracy theory of three-coordinate measuring instruments, as well as Equations (11) and (12), a "Double Accuracy As shown in Figure 3, coordinate system O 50 ; O 60 ; O 70 ; O 80 is respectively an integral coordinate system, a worktable translation coordinate system, a measuring probe rotation coordinate system and a measuring beam translation coordinate system. According to the theoretical solution method of grinding machine precision, it is also concluded that:…”
Section: Double Accuracy Theoretical Analysismentioning
confidence: 99%
“…At the same time, the exploration of machine tool accuracy has also introduced acoustic emission monitoring technology, and it has become a hot topic in the field of advanced processing. Acoustic emission technology has been used for on-line monitoring of grinding processes such as end grinding [11], cylindrical transverse grinding [12], centerless grinding [13], etc. However, most of the authors have neglected the most important step in ensuring the precision of parts while studying the frontier of grinding precision technology.…”
Section: Introductionmentioning
confidence: 99%
“…1. For internal plunge grinding, the grinding power P associated with the tangential grinding force t F can be written as: [18] s t p v F k P = (11) where p k is the coefficient of power, which depends on the grinding conditions, and s v which represents the grinding wheel speed. The normal grinding force n F is proportional to the tangential grinding force t F :…”
Section: Grinding Power Signal Model (Gpsm)mentioning
confidence: 99%
“…However, a means of directly measuring the grinding force has yet to be developed due to the difficulty of installing the measuring instrument at the point of internal plunge grinding [10] . Recently, Chen Jiang et al [11] reported an acoustic emission (AE) model based on grinding force models for the prediction of material removal from a workpiece. Their results indicated that acoustic emission measurements can be used to predict material removal during precision grinding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation